Longitudinal evaluation of the natural history of amyloid-β in plasma and brain. Issue 1 (14th April 2020) - Burnham, Samantha C; Fandos, Noelia; Fowler, Christopher; Pérez-Grijalba, Virginia; Dore, Vincent; Doecke, James D; Shishegar, Rosita; Cox, Timothy; Fripp, Jurgen; Rowe, Christopher; Sarasa, Manuel; Masters, Colin L; et al.
Abstract: Plasma amyloid-β peptide concentration has recently been shown to have high accuracy to predict amyloid-β plaque burden in the brain. These amyloid-β plasma markers will allow wider screening of the population and simplify and reduce screening costs for therapeutic trials in Alzheimer's disease. The aim of this study was to determine how longitudinal changes in blood amyloid-β track with changes in brain amyloid-β. Australian Imaging, Biomarker and Lifestyle study participants with a minimum of two assessments were evaluated (111 cognitively normal, 7 mild cognitively impaired, 15 participants with Alzheimer's disease). Amyloid-β burden in the brain was evaluated through PET and was expressed in Centiloids. Total protein amyloid-β 42/40 plasma ratios were determined using ABtest ® assays. We applied our method for obtaining natural history trajectories from short term data to measures of total protein amyloid-β 42/40 plasma ratios and PET amyloid-β. The natural history trajectory of total protein amyloid-β 42/40 plasma ratios appears to approximately mirror that of PET amyloid-β, with both spanning decades. Rates of change of 7.9% and 8.8%, were observed for total protein amyloid-β 42/40 plasma ratios and PET amyloid-β, respectively. The trajectory of plasma amyloid-β preceded that of brain amyloid-β by a median value of 6 years (significant at 88% confidence interval). These findings, showing the tight association between changes in plasma and brain amyloid-β, support the use of plasma total protein amyloid-β 42/40 plasma ratios as a surrogate marker of brain amyloid-β. Also, that plasma total protein amyloid-β 42/40 plasma ratios has potential utility in monitoring trial participants, and as an outcome measure. Abstract : Total protein amyloid β42/40 plasma ratios determined by the ABtest ® assay were able to effectively map and track longitudinal amyloid PET accumulation. This adds to the body of information that blood-based biomarkers hold utility for diagnosis, prognosis, monitoring and, thus, treatment in the field of Alzheimer's. Graphical Abstract: